2012
DOI: 10.1186/1550-2783-9-22
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an exercise program on acylcarnitines in obesity: a prospective controlled study

Abstract: BackgroundAcylcarnitine (AC) transport dysfunction into the mitochondrial matrix is one of the pathophysiological mechanisms of type 2 diabetes mellitus (DM). The effect of an aerobic exercise (AE) program on this condition in obese subjects without DM is unclear.MethodsA prospective, randomized, longitudinal, interventional study in a University Research Center involved a 10-week AE program in 32 women without DM and a body mass index (BMI) greater than 27 kg/m2. (Cases n = 17; Controls n = 15). The primary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 39 publications
4
11
0
Order By: Relevance
“…This was surprising considering the large body of evidence indicating that in the T2DM or insulin-resistant states, circulating levels of many acylcarnitines, including chain-shortened moieties, are higher (Genuth & Hoppel, 1981;Inokuchi et al 1995;Moder et al 2003;Koves et al 2008;Adams et al 2009;Mihalik et al 2010), and incomplete FAO is observed even in cultured myotubes derived from insulin-resistant models (Koves et al 2008;Aguer et al 2015). Our observations regarding no intervention effects on overnight-fasted, resting plasma medium-chain acylcarnitines are similar to the report of Rodríguez-Gutiérrez et al (2012), who studied the effects of a 10 week aerobic exercise intervention in overweight adults. Resting muscle biopsy results from trained (presumably exquisitely insulin-sensitive) individuals displayed increased, not decreased, acylcarnitine content across chain lengths (Huffman et al 2014).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This was surprising considering the large body of evidence indicating that in the T2DM or insulin-resistant states, circulating levels of many acylcarnitines, including chain-shortened moieties, are higher (Genuth & Hoppel, 1981;Inokuchi et al 1995;Moder et al 2003;Koves et al 2008;Adams et al 2009;Mihalik et al 2010), and incomplete FAO is observed even in cultured myotubes derived from insulin-resistant models (Koves et al 2008;Aguer et al 2015). Our observations regarding no intervention effects on overnight-fasted, resting plasma medium-chain acylcarnitines are similar to the report of Rodríguez-Gutiérrez et al (2012), who studied the effects of a 10 week aerobic exercise intervention in overweight adults. Resting muscle biopsy results from trained (presumably exquisitely insulin-sensitive) individuals displayed increased, not decreased, acylcarnitine content across chain lengths (Huffman et al 2014).…”
Section: Discussionsupporting
confidence: 75%
“…Our observations regarding no intervention effects on overnight‐fasted, resting plasma medium‐chain acylcarnitines are similar to the report of Rodríguez‐Gutiérrez et al . (), who studied the effects of a 10 week aerobic exercise intervention in overweight adults. Resting muscle biopsy results from trained (presumably exquisitely insulin‐sensitive) individuals displayed increased, not decreased, acylcarnitine content across chain lengths (Huffman et al .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown previously that long-chain-acylcarnitines decreased after a long aerobic exercise program in obese women [29]. In contrast, medium-chain acylcarnitines were reported to be increased after moderate intensity exercise [30].…”
Section: Discussionmentioning
confidence: 89%
“…Suppressed adiponectin secretion in the multiparous transition cow could limit FA oxidation and glucose utilization in response to insulin. In support, enhanced plasma adiponectin levels are associated with reduced plasma concentrations of long-chain acylcarnitines (Rodríguez-Gutiérrez et al, 2012), and adiponectin decreases ceramide accumulation in obese mice (Holland et al, 2013). It deserves to be emphasized that serum adiponectin concentrations appear to increase after parturition in primiparous cows (Urh et al, 2019).…”
Section: Leptin Adiponectin and Fibroblast Growth Factor-21mentioning
confidence: 88%